Traffic accidents in the municipality of Misurata for the period 2020/2015 a geographical study (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:This study aims to identify traffic accidents in the municipality of Misurata - Libya, geographically, based on data and annual reports of the Traffic Statistics Office of the Municipal Security Directorate. The study also used the descriptive analytical approach and the historical and statistical approach, to interpret and analyze the data collected on the subject of the study with the aim of knowing the causes of traffic accidents. And their geographical distribution on the roads in the region. One of the most important findings of the study is that the number of accidents in the study area during the study period amounted to approximately 1708 traffic accidents, resulting in 1293 deaths, as well as 485 serious injuries in addition to 106 cases of minor injuries, and also from the results of the study that Most accidents occurred on coastal roads, reaching 693 traffic accidents, which represents 41% of the total accidents in the study area. Also, the age group (25 and under 45) years is the largest age group affected by traffic accident injuries and the most deaths due to accidents, with a total of 482 cases. Deaths, including 432 males and 50 female deaths. The study recommended the necessity of maintaining roads periodically, as well as installing traffic lights and markings, and enforcing the traffic law.                                         Keywords:,,,,.
Keywords: traffic accident; serious injuries; minor injuries; death; age groups